Minat Konsumen Terhadap Beras Organik di Daerah Istimewa Yogyakarta dan Jawa Tengah - Widodo, Widodo; Kamardiani, Diah Rina; Rahayu, Lestari (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2016)
Various cases of food poisoning has caused people to more selective in choosing food by taking into account the health and food safety. Consumer awareness and preferences towards healthy food has resulted an increasing on consumption of organic food. This study aims to explain the consumer perceptions of organic rice, and its effect on consumer buying interest. The study was conducted by analized and interviewed 120 respondents. The binomial logit regression analysis was applied to explain the influence of consumers perception on agricultural products. This research shows the consumers of organic rice come from various groups of people, most of them are from fixed-income consumer, high level of education, and small size family. Consumers of organic rice has a high concern on their family, has a perception on high level of purity, and has high concern on the health of agricultural environment. However, consumers perception on organic farming practices was in moderate category. Organic agricultural products are still perceived as a high price product. Consumer interest on consuming organic rice would increase due to an increasing on consumer concerns on the family, perception of purity, concern on agriculture environmental health, and perception of the practice of organic farming.